2007
DOI: 10.1111/j.2006.0906-7590.04817.x
|View full text |Cite
|
Sign up to set email alerts
|

The distance decay of similarity in ecological communities

Abstract: Biological similartiy typically decreases with geographical distance. Despite the recent attention to the distance decay relationship, there is no consensus on how the relationship varies across organism groups, geographic gradients and environments. We first conducted a quantitative meta-analysis of 401 distance decay relationships across a wide range of organisms, ecosystems and geographical gradients, and then united the effects of categorical and continuous variables on the rate of distance decay using a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
479
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(516 citation statements)
references
References 40 publications
32
479
5
Order By: Relevance
“…Our data analysis proceeded in the following steps, explained in more detail in Soininen et al (2007) and Korhonen et al (2010). First, we checked for possible intercorrelation between the continuous variables, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data analysis proceeded in the following steps, explained in more detail in Soininen et al (2007) and Korhonen et al (2010). First, we checked for possible intercorrelation between the continuous variables, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these temporal datasets (n = 212), we included spatial datasets (n = 17) from published (e.g., meta-review by Soininen et al (2007)) and unpublished sources (ESM Appendix 1). Our criteria for inclusion were that the dataset would contain information on organismal abundances at species or generic levels and that it contains at least four biotic samples.…”
Section: Datamentioning
confidence: 99%
“…Butterflies may be able to disperse to distant locations; however, the distances between the studied communities were not very large. A recent study showed that the similarity between communities begins to decrease at a distance of several hundred kilometers (25). Hence, there may have been an adequate number of migrants between communities regardless of distance.…”
Section: Discussionmentioning
confidence: 99%
“…Community structure at the local scale is viewed along a continuum of dynamics under the metacommunity concept (Leibold et al 2004). Recent meta-analyses have addressed this issue at two levels of abstraction (sensu Legendre et al 2005 andRuokolainen 2006): the variation in community composition (beta diversity) (Cottenie 2005), and the variation in beta diversity across spatial scales (Soininen et al 2007a). Both Cottenie (2005) and Soininen et al (2007a) identiWed four potential determining characteristics of metacommunity type: organism size, sampling spatial scale (including extent and grain size), habitat type and properties of the environment, and organism dispersal type or ability.…”
Section: Introductionmentioning
confidence: 99%